2013
DOI: 10.4265/bio.18.29
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bacterial Community in the Sediment of a Brackish Lake with Oyster Aquaculture

Abstract: The physicochemical properties and bacterial community in sediments of Lake Shiraishi, a lake with brackish water, were characterized to elucidate the influence of oyster farming and seawater and freshwater inflow. Physicochemical analyses suggested the marine origin of the sediment at the mouth of the lake, while higher organic matter load and the resultant anaerobic, reductive condition of the sediments of the inner part were observed. The bacterial community in the sediments reflects these sediment environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Diversity of the benthic microbial community in Shenzhen Bay significantly increases when oysters are present, as has been reported previously [17,47], and Proteobacteria has been identified as a dominant phylum [48]. In our study, Chloroflexi was also among the most abundant phyla, after Proteobacteria.…”
Section: Discussionsupporting
confidence: 87%
“…Diversity of the benthic microbial community in Shenzhen Bay significantly increases when oysters are present, as has been reported previously [17,47], and Proteobacteria has been identified as a dominant phylum [48]. In our study, Chloroflexi was also among the most abundant phyla, after Proteobacteria.…”
Section: Discussionsupporting
confidence: 87%
“…As a key part of global biogeochemical cycles, sulfur cycling mediated by sulfate reduction and sulfur oxidation plays a critical role in nutrient metabolism processes (Li et al ., 2018). Sulfur compounds are important oxidants or reductants for microbial respiration in sediments, which are mainly catalysed by SRB and SOB (Santander‐De Leon et al ., 2013). On the one hand, dissimilatory sulfate reduction mediated by SRB is the dominant anaerobic mineralization pathway of organic matter degradation in sediments (Watanabe et al ., 2013), which consequently release hydrogen sulfide simultaneously into ecosystems (Tian et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of studies on microorganisms in aquaculture have mainly been confined to the composition of microbial community in culture water (Zhao et al, ), sediment (Santander‐De Leon et al, ) and shrimp intestine (Li et al, ; Liu et al, ; Zhang et al, ). Cardona and colleagues reported that rearing‐water bacterial communities influenced the microbiota of shrimp intestine (Cardona et al, ).…”
Section: Introductionmentioning
confidence: 99%